PERBANDINGAN METODE PEMBELAJARAN PROBLEM BASED LEARNING DENGAN METODE MIND MAPPING TERHADAP HASIL BELAJAR BIOLOGI - Hartati Hartati; Ilyas Ismail; Ahmad Afiif (Jurnal Biotek, 2016)
The objectives of this research were to determine the outcome differences learning of students who are taught by the teaching  mthods  Problem Based Learning (PBL) and Mind Mapping in digestive system material of the student in Class XI SMAN 1 Bangkala Western district.jeneponto.This research used quasi Experimental. The research design was nonequivalent control gruop design. The population was all second year student of SMA 1 Bangkala Barat Kabupaten Jeneponto. The population of this research was all students of class XI SMAN 1 Bangkala western district.jeneponto.  The research sampel was class XI IPA2 as the first experimental class XI IPA1 as the second experimental class. Data were collected using achievement test in the form of pretest and posttest. Data were analyzed using  descriptive analysis techniques and inferential statistical analysis techniques.Analysis of the  data showed the learning outcomes student class XI SMAN 1 Bangkala western district.jeneponto. was in digestive system material taught through; the first method of learning (PBL) is in the medium categori, with a percentage of 35 % of the 20  learners and the average value of 79. While the outcomes of Mind Mapping  learning methods  was in middle category, with an average value of 68 with increased 11. The results of the analysis of hypothesis   testing using t-test diperoles thit value = 3.489 and the value ttab with dk= 2.02438. were the value of thit>ttab so H-0 rejected, H1 accepted. Thus there are  differences in learning outcomes of students who are taught through learning methods Problem Based Learning (PBL) with Mind Mapping on the material digestive system in class XI sman 1 Bangkala western district Jeneponto